Primary hyperparathyroidism can generate recurrent pancreatitis and secondary diabetes mellitus – A case report - Nicoleta Mîndrescu; Georgeta Văcaru; Emil Ștefănescu; Loreta Guja; Rucsandra Elena Dănciulescu Miulescu (Journal of Mind and Medical Sciences)
Introduction. Acute or recurrent pancreatitis may be a complication of primary hyperparathyroidism and patients with previous episodes of pancreatitis may develop secondary diabetes mellitus. Case report. We describe the clinical case of a 52-year old Caucasian man diagnosed with chronic recurrent pancreatitis in 2007. The first episode of acute pancreatitis occurred in 2002, followed by another 4 episodes in 2004 and 2007. In 2004, papilosfincterectomy was implemented with a stent mount that was removed one month later. In 2005, the patient underwent a surgical intervention for the diagnosis of chronic lithiasis, and cholecystectomy was performed. Additional investigations on the etiology of recurrent chronic pancreatitis, initially diagnosed as idiopathic, revealed elevated values of total serum calcium, serum parathormone, and the presence of a parathyroid adenoma in the right lower pole of the thyroid. In September 2007, parathyroidectomy was performed with a favorable evolution and the remission of the acute pancreatitis episodes. The patient had not had any family history of diabetes; in 2017 he was diagnosed with diabetes. Conclusion. In cases of recurrent pancreatitis, screening for hyperparathyroidism is recommended. Metabolic evaluation is required, because the risk of developing diabetes in patients with recurrent pancreatitis is high.